Relating productivity and trade 1980-2000: a chicken and egg analysis - Eleanor Doyle; Inmaculada Martínez-Zarzoso (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
Given the nature and range of investigations of the trade/productivity relationship, we now know that possible reverse causation must be a consideration in empirical research. Indeed, some research finds that estimates of productivity gains attributed to trade capture instead the roles of institutions and geography. Here we estimate the relationship between productivity and trade for a panel of countries over the period 1980 to 2000 using instrumental-variables estimation of a productivity equation. The endogeneity of trade and institutional quality is accounted for by using instruments. We extend the specification used by Frankel and Romer (1999) using real openness as the measure of trade (following Alcala and Ciccone, 2004). The trade instrument is based on a gravity equation. The instruments for institutional quality come from Gwartney, Holcombe and Lawson (2004). This approach allows for identification of channels through which trade and production scale affect productivity.
Keywords: 330